Mapping public appraisals of carbon dioxide removal. (September 2022) - Bellamy, Rob
Highlights: I develop a novel method for public appraisal of five policy relevant CDR methods. The British public support the inclusion of CDR in UK climate policy. 'Natural' CDR is preferred but likely a result of prevailing Romanticist thought. 'Technological' CDR is less polarising and may be held back by the nature framing. Highest support is from egalitarians, older people, men, and higher social grades. Abstract: Efforts to deliver on net zero emissions targets are set to rely on carbon dioxide removal (CDR) methods. Democratic, trustworthy and socially intelligent research, development, demonstration and deployment of CDR methods in aid of net zero will be highly dependent on how different publics evaluate them, and ultimately which groups support or oppose them. This paper develops a novel, nationally representative method for the multi-criteria appraisal of five policy relevant CDR methods – plus an option not to pursue CDR at all – by members of the British public (n = 2, 111). The results show that the public supports the inclusion of CDR in UK climate policy. CDR methods often characterised as 'natural' or 'nature-based' are appraised more highly than 'technological' ones, in the descending order: habitat restoration, afforestation, wood in construction, bioenergy with carbon capture and storage, and direct air carbon capture and storage. Yet, there is no significant disagreement in the appraisal of technological methods and they therefore may be less polarizing, suggesting that popular preconceptions of what is natural – and therefore more attractive – may be holding them back. CDR methods being mainly developed by public sector and non-governmental organisations are also appraised more highly than those being developed by private interests. Regional differences in option appraisal reveal where particular CDR methods are more or less likely to be supported or opposed; stressing the importance of matching physical requirements for CDR with appropriate social contexts. Demographic and socio-economic analyses show that people who appraise CDR methods most highly tend to be older respondents, male, or of a higher social grade. Finally, those with hierarchical worldviews and who voted 'leave' in the UK's referendum on EU membership are less supportive of CDR than those with egalitarian worldviews and who voted 'remain'.